Changes in farmers' income in Fuling District of Chongqing China from 2018 to 2028: A grey prediction method perspective. (October 2019) - Peng, J Q
Abstract: Urbanization development can have a great impact on farmers income structure. Through empirical analysis, the results of this paper show that with the development of urbanization the per capita disposable income of farmers in Fuling District will reach70, 890.69 yuan per person by 2028, nearly five times that of 2017. The influence of urbanization rate on various income sources of Fuling farmers are as follows: family business income, wage income, transfer income, and property income. The government should increase investment in rural education, promote the improvement of farmers' quality, accelerate infrastructure construction, increase support for agriculture, vigorously promote accurate poverty alleviation, promote the increase of farmers' family business income, and steadily increase farmers' wage income.